Methaemoglobinaemia associated with the use of cocaine and volatile nitrites as recreational drugs: a review - Hunter, Laura (Blackwell Science Inc, 2011)
Methaemoglobinaemia can cause significant tissue hypoxia, leading to severe, potentially life-threatening clinical features and/or death. Over recent years there have been increasing reports of methaemoglobinaemia related to recreational drug use. There have been 25 articles describing methaemoglobinaemia related to recreational use of volatile nitrites (poppers) and more recently, four reports of methaemoglobinaemia in association with recreational cocaine use. In this article we discuss the mechanisms by which methaemoglobinaemia occurs in relation to the use of both volatile nitrites and cocaine, and summarize the published cases of recreational drug-related methaemoglobinaemia. The volatile nitrites can cause methaemoglobinaemia directly through their activity as oxidizing agents. However, with cocaine, methaemoglobinaemia is related to adulterants such as local anaesthetics or phenacetin, rather than to the cocaine itself. Clinicians managing patients with acute recreational drug toxicity should be aware of the potential for methaemoglobinaemia in these patients, particularly in patients with cyanosis or unexplained low oxygen saturations on pulse oximetry, and ensure that appropriate and timely management is provided, including, where appropriate, the use of methylthioninium chloride (methylene blue).